Japanese Accent Pronunciation Error by Japanese Learners in Elementary and Intermediate Level - Dimas Maheswara; Hari Setiawan; Andi Irma Sarjani (Universitas Pendidikan Indonesia (Indonesia University of Education), 2022)
This research discusses errors in the pronunciation of Japanese accents by Japanese learners. This study aims to determine the forms and causes of accents pronunciation errors in Japanese learners as well as Japanese learners’ comprehension of Japanese accent. The data used are speech data (word and sentence) of 18 people who are students of Japanese literature at a private university in Jakarta, in their 3rd and 4th years (hereafter written as respondents). As comparison data, this research uses Japanese native speaker data from Tokyo and electronic speech data from OJAD (Online Japanese Accent Dictionary). This research used a qualitative research method. Praat application also used to get a detailed visual description of Japanese speech from respondents. The results of this research found a form of error in the form of accent changes that do not match the speech data per word and sentence. The cause of accent errors was the lack of attention to the accent and the lack of learning about accents in the respondent’s learning environment. It was also found that 80% of respondents had minimal understanding of Japanese accents.